Visionary Leadership of Principals in Increasing School Quality at SMKN 1 Sambas - Tajmi Musytari; M. Chiar; Wahyudi Wahyudi (JETL (Journal of Education, Teaching and Learning), 2019)
This study is aimed at objectively looking at the visionary leadership of principals in improving the quality of schools in Sambas 1 State Vocational School (SMKN 1 Sambas). This study uses a qualitative approach. The results showed that SMKN 1 Sambas was a school that was guided by a vision to improve school quality. Improving the quality of schools at SMKN 1 Sambas is achieved through a good school management process by the principal. Based on the findings, researchers suggest: 1) In implementing the school activity program there needs to be control and evaluation of each program implemented. 2) It is recommended to periodically rotate teachers and employees who are given additional assignments. 3) Increase the discipline and commitment of teachers and employees in carrying out the duties and responsibilities assigned to them. 4) Schools need to hold special meetings with parents who discuss the Vision, Mission, and Objectives of the school and convey the importance of the support and role of parents in the education process of their children in school.